Harvesting experience: a reappraisal of the U.S. - Brunner, Ronald D.; Klein, Roberta (1999)
For mitigating climate change and adapting to whatever impacts we cannot avoid, there are no politically feasible alternatives to improvements in the U.S. Climate Change Action Plan at this time or for the foreseeable future. Yet improvements in the Action Plan have been obstructed by the diversion of attention and other resources to negotiating a binding international agreement, to developing a predictive understanding of global change, and to documenting the failure of the Action Plan to meet its short-term goal for the reduction of aggregate greenhouse gas emissions. Continuous improvements depend upon reallocating attention and other resources to the Action Plan, and more specifically, to the many small-scale policies that have already succeeded by climate change and `no regrets' criteria under the Action Plan. Sustaining the effort over the long term depends on harvesting experience from these small-scale successes for diffusion and adaptation elsewhere on a voluntary basis. - Reproduced
Keywords: Harvesting - United States; Climatic change - United States; Climatic change